Petrographic, Geochemical and Geothermobarometric Characteristics of The Late Cretaceous Dioritic Gabbros in The Northwestern Pertek (Tunceli) - Erturk, Mehmet Ali (Gazi Univ, 2025)
The northwestern Pertek region (Tunceli), located within the Eastern Anatolia segment of the Southeastern Anatolian Orogenic Belt, is characterised by Late Cretaceous dioritic gabbro intrusions. These intrusive rocks exhibit medium to coarse-grained crystalline textures and are mainly composed of plagioclase and amphibole, with minor amounts of pyroxene. The dioritic gabbros display tholeiitic affinity, mafic compositions, and metaluminous character. Trace element diagrams show pronounced positive anomalies in large-ion lithophile elements (LILE) such as Cs, Rb, Ba, Th, and U, whereas negative anomalies are evident in high field strength elements (HFSE) such as Nb, Ta, and Ti, suggesting a subduction-related magmatic setting. Chondrite-normalised rare earth element (REE) patterns are relatively flat, with limited enrichment in light rare earth elements (LREE), indicating highdegree partial melting under spinel-facies control. Geothermobarometric calculations based on plagioclase-melt and amphibole chemistry reveal crystallisation conditions, with plagioclase indicating high temperatures (similar to 1284 degrees C) and pressures (similar to 11 kbar), while amphiboles crystallised at lower temperatures (955-1037 degrees C) and shallower pressures (1.87-2.12 kbar). These values suggest that plagioclase formed at deeper levels and amphibole crystallised during later, shallower stages of magma evolution. Tectonomagmatic discrimination diagrams indicate that the rocks were emplaced in an active arc magmatic setting. Overall, the findings demonstrate that the dioritic gabbros of northwestern Pertek represent mafic magmatism associated with a subduction zone active during the closure of the southern branch of the Neotethys in the Late Cretaceous.
Keywords: Pertek (Tunceli); Late Cretaceous; arc-related magmatism; geothermobarometer